PENGARUH SERVICESCAPE TERHADAP MINAT KUNJUNG ULANG MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASI - Shah, Mohamed Ashraff; Handrito, Radityo Putro (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2022)
This study aims to determine the effect of servicescape on revisit intention which are mediated by customer satisfaction on cafe visitors in Malang City. This type of research is explanatory research that seeks to explain the relation between variables based on hypothesis testing. This study used a sample of 385 respondents based on the Cochran formula. The distribution of the questionnaires was carried out online through google form. The data analysis technique in this research is using SPSS and the process analysis method by Hayes. The results of this study are servicescape has a significant effect on customer satisfaction, customer satisfaction has a significant effect on interest in revisit intention, servicescape has a significant effect on revisit intention, and customer satisfaction mediates the effect of servicescape on revisit intention. Based on these results, it can be concluded that there is a partial mediation effect because the servicescape can directly affect revisit intention without going through customer satisfaction due to the servicescape's strong appeal to cafe visitors. So, it can be formulated research implications in the form of recommendations for cafe themes and three keys to developt cafe in Malang City.